Immunological possibilities of diagnostics and prognosis of aseptic and infected local complications of acute pancreatitis development - Desiateryk, V. I.; Maltsev, D. V.; Кrykun, M. S.; Shapovaliuk, V. V.; Shkura, M. M. (Zaporozhye Medical Journal, 2019)
The aim. To substantiate the possibility of diagnosis and prediction of aseptic and infected local complications of acute pancreatitis (AP) by determining the level of immunoglobulins of class G. Materials and methods. 30 patients with AP (oedematous and necrotic form) were examined. The control group consisted of patients scheduled for inguinal hernia, varicose vein and breast fibroadenoma surgery (n = 10). Laboratory and immunological studies were carried out three times: the 1st study – upon admission; the 2nd – on the 7th day; the 3 – on the 14th day. An enzyme-linked immunoglobulin analysis of IgG subclasses (G1, G2, G3, G4) was performed in the main study group. Results. Median survival time is 12 days (95 % CI 2.0–28.0) among all examined patients. This time decreases in immunoglobulins deficiency and is 10 days (95 % CI 10.0–71.0) in total IgG level decrease. When comparing groups with a lower level of immunoglobulins and normal, this trend is reflected in all subclasses, and a statistically significant difference between them is detected for IgG4. There is a significant difference (p = 0.049) in Kaplan-Mayer's curves in terms of reducing survival without complications in patients with low IgG4 level (median survival 2.0 days, 95 % CI 1.0–17.0) compared to normal and high its level (Me = 28.0; 95 % CI 10.0–7.0). Survival without complications of the examined patients increases statistically significantly with an increase in the total level of immunoglobulins – RR = 0.91 (95 % CI 0.11–0.98). The probability of complication in and after hospitalization for a patient with GP is lower with the most increase in IgG4 – RR = 0.02 (95 % CI 0.001–0.650). Consequently, the higher level of immunoglobulins in patients, the less the risk of getting complications. Patients with low IgG4 level are more likely to develop complications than patients with normal or elevated IgG4 level. That is, the level of subclass IgG4 can be considered as a diagnostic criterion of complications development and one of their occurrence predictors. Conclusions. Definition of IgG dynamics in patients with AP provides new opportunities for predicting the development of local complications of AP. The level of IgG4 may serve as an additional diagnostic criterion for the local AP complications development.